Local exact controllability of an age structured problem modelling phenotypic plasticity in mosquito behaviour - Li, Lin Lin; Ferreira, Cláudia Pio [UNESP]; Ainseba, Bedreddine (Elsevier, 2022)
In this paper, we investigate the local exact controllability of an age structured problem modelling the ability of malaria vectors to shift their biting time to avoid the stressful environmental conditions generated by the use of indoor residual spraying (IRS) and insecticide-treated nets (ITNs). We establish a new Carleman's inequality for our age diffusive model with nonlocal birth process and periodic biting time boundary conditions. Some estimates of the theory of parabolic boundary value problems in Lk are used to get the controllability.
Keywords: An age structured model; Biting time shift; Local exact controllability